DIDACTIC POSSIBILITIES OF ELECTRONIC LEARNING TOOLS IN THE PROCESS OF TEACHING MUSIC (Web of Teachers: Inderscience Research, 2025)
The article discusses the didactic possibilities of electronic educational means in the process of teaching music. Their role in the formation of students' musical thinking, auditory perception, creative activity and independent learning is revealed. The author conducts a theoretical analysis of the effectiveness of the use of digital technologies, interactive programs, multimedia resources and mobile applications in music education. Special attention is paid to the digital competence of the teacher, the principles of visualization, reflection and individualization. The study shows not only the educational, but also the educational value of electronic resources, determining their prospects in the modernization of music education